The Impact of Using Documented but Uncharged Offense Data on JSORRAT-II Predictive Validity. (March 2017) - Ralston, Christopher A.; Sarkar, Amar; Philipp, Grace T.; Epperson, Douglas L.
Following the implementation of sexual offender notification laws, researchers have found a drop in the rate of prosecutions and an increase in plea bargains for sexual offenses committed by male juveniles. This type of prosecutorial hesitation has implications for the predictive validity of sexual recidivism risk assessments, such as the Juvenile Sexual Offender Recidivism Risk Assessment Tool–II (JSORRAT-II), that require data from officially adjudicated offenses in the scoring of several items. The present study sought to test the impact of including data from documented but uncharged (DBU) sexual offenses in the scoring of the JSORRAT-II on its predictive validity using an exhaustive sample of 1, 095 juveniles who offended sexually from the states of Iowa and Utah. Although sexual recidivists had significantly more DBU data, the inclusion of those data did not improve the predictive validity of the tool. The authors discuss additional reasons why changes in prosecutorial practice might remain confound in risk assessment studies and suggest future research to investigate those hypotheses.